Use of Lactobacillus acidophillus R0052 and Lactobacillus rhamnosus R0011 Probiotic Strains in Children with Burn Injures - Patsera, Maryna; Skrypnykova, Yanina; Ivanko, Oleg; Пацера, Марина Вікторівна; Скрипникова, Яніна Семенівна; Іванько, Олег Григорович; Пацера, М. В.; Скрипникова, Я. С.; Иванько, О. Г. (My University, 2016)
Today, burn injury is second most frequent diagnosis in all children hospitalized with injuries. The main cause of death in cases of extensive deep burns is burn infection that occurs in 23 to 82 % of all burn units’ patients. Antibacterial treatment rationality is of great importance in fighting the generalized infections. This paper is aimed at scrutinizing the incidence and course characteristics of the antibiotic-associated diarrhea (AAD) in burn patients, as well as the possibility of its prevention in children receiving antibacterial treatment in the Regional Burn Unit of Zaporizhzhia. During 2012–2015, we have observed 438 children with burn injuries, who received antibiotics. We observed children receiving antibiotics and examined over hospitalization time by detection of the highly specific for antibiotic-associated diarrhea A + B Clostridium difficile toxins in stool, which allowed diagnosing the enterocolitis due to Clostridium difficile associated with antibiotics administration (A4.07, ICD-10). AAD prevention methods have been developed, among which preventive (from the first hours of hospitalization) administration of oral probiotic agent containing Lactobacillus acidophilus R0052 and Lactobacillus rhamnosus R0011 probiotic strains as a part of the Lacidofil® preparation dosed by age should be considered a major one. Prophylactic prescription of probiotic strains with antitoxic action against Clostridium difficile had reduced the incidence of antibiotic-associated diarrhea in children and the severity of its symptoms by 3.4 times. На сьогодні опіки посідають друге місце серед усіх травм дітей. Основною причиною летальних наслідків у випадку виражених та глибоких опіків є інфекція, що виникає у 23–82 % усіх випадків опіків. Раціональна антибактеріальна терапія має велике значення в боротьбі з генералізованою інфекцією. Метою цього дослідження було ретельне вивчення епідеміології та характеристики антибіотик-асоційованої діареї (ААД) у хворих дітей з опіками, а також можливість запобігання цій діареї, що виникала внаслідок антибактеріальної терапії в пацієнтів Обласного опікового відділення м. Запоріжжя. Протягом 2012–2015 років ми спостерігали 438 дітей з опіковими травмами, які приймали антибіотики. У цих госпіталізованих дітей було знайдено специфічні для ААД Clostridium difficile токсини А + В у фекаліях. Це дозволило діагностувати Clostridium difficile-ентероколіт, пов’язаний з прийомом хворими антимікробних препаратів (A4.07, МКБ-10). Розроблено профілактичні методи AAД, а саме призначення з перших годин перебування в стаціонарі per os пробіотичного засобу Lactobacillus acidophilus R0052 і Lactobacillus rhamnosus R0011 у складі препарату Lacidofil®. Використання пробіотичних штамів з антитоксичною активністю щодо Clostridium difficile скорочує в 3,4 раза число випадків антибіотик-асоційованої діареї в дітей з опіками та зменшує тяжкість її симптомів. Сегодня ожоговая травма занимает второе место среди всех травм детей. Основной причиной смерти в случае обширных глубоких ожогов является ожоговая инфекция, которая осложняет заболевание в 23–82 % случаев всех ожогов. Рациональная антибактериальная терапия имеет большое значение в борьбе с генерализованной инфекцией. Целью этого исследования было тщательное изучение распространенности и характеристики антибиотик-ассоциированной диареи (ААД) у больных с ожогами, а также возможность ее предотвращения у детей, получавших лечение антибактериальными препаратами в Областном ожоговом отделении города Запорожье. В течение 2012–2015 годов мы наблюдали 438 детей с ожоговыми травмами, получавших антимикробные препараты. У детей, находящихся на госпитализации и принимавших антибиотики различных групп, были обна ружены специфические для AAД Clostridium difficile токсины А + В в стуле. Это позволило диагностировать Clostridium difficile-энтероколит, связанный с назначением антибиотиков (A4.07, МКБ-10). Разработаны методы профилактики AAД, а именно назначение с первых часов пребывания в стационаре per os пробиотических штаммов Lactobacillus acidophilus R0052 и Lactobacillus rhamnosus R0011 в составе препарата Lacidofil®, дозированных по возрасту. Использование про- биотических штаммов с антитоксическим действием против Clostridium difficile сокращает в 3,4 раза число случаев антибиотик-ассоциированной диареи у детей с ожогами и уменьшает тяжесть ее симптомов.
Досвід використання пробіотичних штамів Lactobacillus acidophilus r0052 та Lactobacillus rhamnosus r0011 у дітей з опіковою травмою
Опыт использования пробиотических штаммов Lactobacillus acidophilus r0052 и Lactobacillus rhamnosus r0011 у детей с ожоговой травмой
Keywords: Gastroenterological Diseases in Children; children; burn injury; antibiotic-associated diarrhea; Lactobacillus acidophilus R0052 and Lactobacillus rhamnosus R0011 probiotic strains; діти; опікова травма; антибактеріальна терапія; антибіотик-асоційована діарея; пробіотичні штами Lactobacillus acidophilus R0052 та Lactobacillus rhamnosus R0011; дети; ожоговая травма; антибиотик-ассоциированная диарея; пробиотические штаммы Lactobacillus acidophilus R0052 и Lactobacillus rhamnosus R0011